2024
DOI: 10.3389/fpubh.2023.1281323
|View full text |Cite
|
Sign up to set email alerts
|

Exercise or lie down? The impact of fitness app use on users' wellbeing

Jie Cai,
Gang Li

Abstract: IntroductionThe use of fitness apps is becoming more and more widespread, and its impact on people's well-being has received more and more attention.MethodsThe relationship between fitness app use and users' well-being and the influence mechanism was explored using structural equation modeling with upward social comparison as the mediating variable and self-control as the moderating variable.ResultsThe questionnaire survey of 1,452 fitness app users over 18 years old shows that: (1) fitness app use is associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In this context, individualized counselling and goal setting were previously identified as factors promoting a successful health app [59]. Previous studies on apps have shown that mental health issues [60] and physical activity status [61,62] may also be improved by apps. In the present pilot study, we did not use instruments fit to sensitively detect more subtle changes in both domains.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, individualized counselling and goal setting were previously identified as factors promoting a successful health app [59]. Previous studies on apps have shown that mental health issues [60] and physical activity status [61,62] may also be improved by apps. In the present pilot study, we did not use instruments fit to sensitively detect more subtle changes in both domains.…”
Section: Discussionmentioning
confidence: 99%